This post stated an easy Number Theory question regarding the number of solutions of the Diophantine equation .
I decided to make the question a bit more interesting:
Characterize all positive integer solutions to given that .
Indeed, the following is also true:
Given that are positive integers that satisfy both and , then it follows that .
My solution is elementary, but well-hidden. I await your solutions.
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
The first solution that comes to my mind:
For Diophantine equation a2=bc for a,b,c being positive integers, we can parametrize the solutions as (a,b,c)=(kmn,km2,kn2) where k,m,n are positive integers and gcd(m,n)=1. Essentially, take the GCD of b,c, which is k; this must divide a as well. For the rest, each of kb,kc must be squares; an unmatched divisor of kb must also exist in kc (to make a square), but this contradicts that the two are now relatively prime (since we have removed their GCD).
Using this to the equation x(x+z)=y2, we have x=km2,x+z=kn2,y=kmn. Since z>0, we have kn2>km2 or n>m.
The condition is:
2y−2x1111≥z−1≥z+2x−2y≥x+(x+z)−2y≥km2+kn2−2kmn≥k(n−m)2
We know that k≥1 as it's a positive integer. We also know that n>m, and since m,n are integers, we have n−m≥1. Thus equality is achieved; we have k=1,n−m=1. In other words, (x,y,z)=(m2,m(m+1),2m+1). This can be verified to satisfy the equation for all positive integer m.
It is clear from x(x+z)=y2 that x, x+z and y are in G.P. But since they are distinct, it follows that x<y<x+z. So, x, y and x+z are in G.P. with intial term a=x and with common difference r=yx+z. Now, a+ar2>2ar, I mean that the sum of the extremes is greater than twice the middle term in a G.P. with three terms (Equality does not hold since r>1.) So,
(x+z)+x>2y z>2y−2x z−1≥2y−2x
But given that 2y−2x≥z−1. It holds that 2y−2x=z−1.
Nice solutions Surya Prakash , Ivan Koswara . Here is mine:
Note that 2y−2x≥z−1⟹y≥x+2z−1
However, we also know trivially that y2=x(x+z)<(x+2z)2 so we have the following bounds: x+2z−1≤y<x+2z Since y is an integer, it follows that z must be odd and y=x+2z−1. Thus we have 2y−2x=z−1
This also means z=2t+1. Solving x(x+z)=(x+2z−1)2 gives x=t2, and finally y=t2+t so our parameterization is (x,y,z)=(t2,t2+t,2t+1)